Teacher Self-Efficacy Training to Improve Teachers’ Work Engagement - Imanda, Imanda (Jurnal Pendidikan Ilmu Sosial, 2021)
This experimental study examines the effect of teacher self- efficacy training to increase work engagement among teachers. Participants in this training were 16 teachers from the level of playgroup/kindergarten, and lower grade primary level. Work Engagement is measured using the Work and Well Being Survey (UWES) attitude scale, while Teacher Self Efficacy is measured using the Norwegian Teacher Self Efficacy Scale (NTSES). The results showed that there were differences in the level of understanding of participants' knowledge about work engagement and teacher self-efficacy before and after training, through the results of statistical tests with the Wilcoxon non-parametric SPSS 16.0 program 0.001 (sig. 0.05). Based on the correlation test for the two variables, the results of the pre-test (0.502) and post-test (0.507) were obtained. Based on T-test, the results of the significance level of work engagement is 0.183 (sig. 0.05) and the significance level of teacher self-efficacy is 0.131 (sig. 0.05), which means that there is no difference in the level of work engagement and teacher self-efficacy on the participants before and after attending the training. The finding shows the training materials provide new insights for the training participants in terms of knowledge level. However, the training has not increased work engagement level, probably caused by the matter of the social desirability bias and performance bias in this research.